Inflation, growth and monetory policy in South Africa: application of non-linear models - Tshuma, Mthokozisi Mncedisi (My University, 2018)
This thesis intends to shed new light on the conduct of South Africa’s central bank behavior. The thesis analyses the monetary policy conduct and the use of non-linear rules in South Africa. Furthermore, it scrutinizes the applicability of non-linear rules in characterizing the monetary policy behaviour in South Africa. Over and above the introductory chapter, the thesis comprises five main independent chapters, namely: chapters 2, 3, 4, 5, and 6. Chapter 7 cover conclusions. Chapter 21 determines the applicability of a nonlinear Taylor rule in characterizing the monetary policy behavior of the South African Reserve Bank (SARB), using a logistic smooth transition regression approach. The evidence suggests the nonlinear Taylor rule is the most appropriate model to describe the monetary policy conduct of the South African Reserve Bank. In Chapter 3, nonlinear models are used to analyse the nonlinear relationship among monetary policy, economic activity and financial instability, which is an extension of the previous chapter (Chapter 2). Two models (threshold regression and smooth transition) were used to analyse the role of financial condition in the interest setting by monetary authorities. The findings indicate that there is an inflation threshold level of 6.2 percent above, which the central bank adjusts its interest rate to maintain price stability. The results provide enough evidence that the monetary policy followed by the South Africa Reserve Bank (SARB) can be described by a nonlinear Taylor rule. The thesis extends the analysis to determine the differential effects of inflation on GDP growth based on the estimated inflation. The purpose is to show that inflation is detrimental to economic growth at elevated levels. As a consequence, chapter 4 identifies the threshold effect of inflation on economic growth in South Africa. The estimated threshold model reveals that in South Africa, there is a non-linear relationship between inflation and economic growth. This implies that above the threshold level, inflation has a negative statistically significant effect on economic growth. These results may help policymakers in maintaining low inflation, which is below the threshold level to mitigate its negative effect on economic growth. Chapter 5 examines the effect of inflation variation on financial depth-growth relationship using a smooth transition regression model. The findings show that financial development and economic growth are non-linearly related with an increase in inflation beyond the threshold (at 4.3 percent) negatively impacting on economic growth. Therefore, financial development has a positive impact on economic growth when inflation is below the threshold of 4.3 percent, though above the threshold there is a negative relationship between financial development and economic growth. Chapter 6 examines the exchange rate pass through effect to headline CPI inflation, producer price inflation and import price inflation in South Africa. The analysis of exchange pass through effect is relevant in the context of South Africa as decisions of monetary policy makers take into account changes in domestic prices emanating from exchange rate adjustments. For the purposes of analysis, this chapter estimates a Threshold Vector Autoregression (TVAR) to capture switches between the low and high inflation regimes implied by the theoretical literature with inflation rate as a transition variable. Using nonlinear impulse response functions, this chapter evaluate the dynamics implied by the threshold model. Findings reveal that prices (headline CPI inflation, producer price inflation and import price inflation) react strongly to a positive one unit exchange rate shock both below and above the threshold level of the inflation rate.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in Fulfillment of the Requirements for the Degree of Doctor of Philosophy, May 2018
Keywords: Monetary policy--South Africa; Inflation (Finance)--South Africa